Teaching pharmacology in china: challenges faced by students and lecturer in the new era - Nur Aliana Hidayah Mohamed (Journal of University Medical & Dental College, 2025)
The rapid advancement of medical science in China has made teaching pharmacology increasingly challenging. Traditional teaching methods, mainly relying on didactic lectures and experimental sessions, are no longer sufficient to meet the diverse learning needs of modern students or to keep pace with newly developed drugs. Educators are required to continuously update their knowledge and adopt innovative teaching strategies such as problem-based learning (PBL), team-based learning (TBL), and flipped classrooms (FC). These approaches have been shown to improve student engagement, attendance, academic performance, and overall satisfaction. However, language barriers remain a major challenge, as pharmacological terminology is largely derived from Greek and Latin. To address this issue, strategies such as breaking complex terms into smaller components and implementing flipped classroom models are recommended. Pharmacology plays a vital role in medical education by linking drug mechanisms with clinical application. This paper highlights innovative teaching methods, technology-based tools, collaborative learning, and bilingual support to enhance pharmacology education in China.